Analisis Nilai-Nilai Qur’ani dalam Syair Tombo Ati: Pendekatan Penafsiran Intertekstualitas Julia Kristeva (L. 1941 M) - Dini Siti Habibah; Ahmad Syukron; Samsul Ariyadi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
The Tombo Ati poem is one of the Javanese cultural heritages that carries profound spiritual and moral meanings, rich in Islamic values and spirituality. This study aims to analyze the Qur’anic values contained in the poem using Julia Kristeva’s (b. 1941) intertextuality theory as the interpretative framework. Through this approach, the research explores the intertextual relationship between the Tombo Ati text and Qur’anic teachings as its primary source of values. The study employs a qualitative descriptive method with textual analysis. The findings reveal a strong connection between Tombo Ati and Qur’anic values, including the reinforcement of monotheism (tawḥīd), sincerity in worship, friendship with the righteous, self-control, and gratitude to Allah Almighty. From Kristeva’s intertextual perspective, the poem exists in dialogue with the Qur’an, and these values form the foundation of its meaning and moral message. The study concludes that Tombo Ati serves as an effective medium for internalizing Qur’anic values through local cultural expression, making it relevant for education, da’wah, and character development.